Dyskeratosis Congenita: A Report of Two Cases - Anila Karunakaran; Rathy Ravindran; Mohammed Arshad; M. Kodanda Ram; M. K. Shruthi Laxmi (Case Reports in Dentistry)
Oral manifestations play an important role in the diagnosis of many systemic conditions. Dyskeratosis congenita (DC) is a rare genodermatosis which exhibits oral leukoplakia, nail dystrophy, and reticular skin pigmentations as its primary features. DC has increased risk of developing constitutional anemias and malignancies and early diagnosis enables the patient to be monitored and proper interventional therapy to be instituted. Hence, dentists need to be aware of the various manifestations of this fatal syndrome. Only few cases have been reported on DC in the dental literature. Two cases of DC are reported here with a brief review of the literature.